Labor Standards for Nontraditional Kansas Crops - Langemeier, Larry N. (My University, 1998)
This publication examines the labor standards for different nontraditional crops produced in Kansas.
MF2359_1998_10
Keywords: MF2359; Economics; Crops; MF